The role of neophobia in a pioneer olfactory enrichment for amazons, macaws, and toucans - Hernández, Carmen; Barja, Isabel (Revista de Biología Tropical, 2024)
Introduction: Despite sensory enrichment being critical for ensuring the well–being of captive wild animals, smells are not being included in enrichment protocols for birds. For this group, neophobia can be a problem when it comes to implementing new enrichment devices. Objective: To explore how participation in an olfactory enrichment and latency times varies between bird taxonomic groups (Amazona spp. / Ara spp. / Ramphastos spp.). Methods: We exposed 257 birds to a scent enrichment, and we recorded which individuals engaged with it and the time they took to interact with it. Results: We discovered that participation by toucans in the enrichment was higher compared to amazons and macaws. Furthermore, latency time to interact with the enrichment was higher in amazons that in the other species. Our findings could suggest that toucans are neophilic species which could benefit from higher exploration rates. Amazons on the contrary seem to be particularly neophobic, possibly because of their less opportunistic feeding habits compared to toucans and their higher vulnerability to predation compared to macaws. Conclusion: These results point out that toucans would be more inclined to engage in environmental enrichments, while a more natural design using smells inside familiar objects could be a more successful enrichment for psittacids